A primate-specific isoform of PLEKHG6 regulates neurogenesis and neuronal migration - O’Neill, Adam C; Kyrousi, Christina; Klaus, Johannes; Leventer, Richard J; Kirk, Edwin P; Fry, Andrew; Pilz, Daniela T; Morgan, Tim; Jenkins, Zandra A; Drukker, Micha (Cell reports, 2018)
The mammalian neocortex has undergone remarkable changes through evolution. A consequence of such rapid evolutionary events could be a trade-off that has rendered the brain susceptible to certain neurodevelopmental and neuropsychiatric conditions. We analyzed the exomes of 65 patients with the structural brain malformation periventricular nodular heterotopia (PH). De novo coding variants were observed in excess in genes defining a transcriptomic signature of basal radial glia, a cell type linked to brain evolution. In addition, we located two variants in human isoforms of two genes that have no ortholog in mice. Modulating the levels of one of these isoforms for the gene PLEKHG6 demonstrated its role in regulating neuroprogenitor differentiation and neuronal migration via RhoA, with phenotypic recapitulation of PH in human cerebral organoids. This suggests that this PLEKHG6 isoform is an example of a primate-specific genomic element supporting brain development.